2020
DOI: 10.1097/md.0000000000020466
|View full text |Cite
|
Sign up to set email alerts
|

Segmental zoster paresis of unilateral upper extremity

Abstract: Rationale: Segmental zoster paresis (SZP) is a relatively rare neurologic complication of herpes zoster (HZ), and is characterized by focal asymmetric motor weakness in the myotome that corresponds to skin lesions of the dermatome. The upper extremities are the second most commonly involved regions after the face, and predominantly involve proximal muscles. The pathogenesis of SZP remains unclear; however, most of the reports indicate that it is the inflammation because of the spread of the herpes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
(42 reference statements)
0
16
0
6
Order By: Relevance
“…[9][10][11][12][13] When varicella-zoster virus invades the anterior nerve root, patients experience decreased muscle strength and motor dysfunction, which usually occurs within a few weeks after the appearance of the rash. 14 Since Broadbent first reported a case of motor dysfunction caused by cervical herpes zoster in 1866, a number of cases have been reported, [15][16][17][18] including literature reporting that the incidence of motor dysfunction in patients with herpes zoster was only 0.3%-5.0%, but Mondelli et al found that more than half of the patients with herpes zoster had limb motor nerve involvement, indicating that a large number of patients were missed. 19 In our study, when MRC score rather than electromyography was used, the overall incidence of motor dysfunction reached 4.59% (58/1264), which may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] When varicella-zoster virus invades the anterior nerve root, patients experience decreased muscle strength and motor dysfunction, which usually occurs within a few weeks after the appearance of the rash. 14 Since Broadbent first reported a case of motor dysfunction caused by cervical herpes zoster in 1866, a number of cases have been reported, [15][16][17][18] including literature reporting that the incidence of motor dysfunction in patients with herpes zoster was only 0.3%-5.0%, but Mondelli et al found that more than half of the patients with herpes zoster had limb motor nerve involvement, indicating that a large number of patients were missed. 19 In our study, when MRC score rather than electromyography was used, the overall incidence of motor dysfunction reached 4.59% (58/1264), which may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of radiculopathy could be estimated through CMAP amplitude or the amount of ASA in the involved muscles. Several previous studies diagnosed segmental zoster radiculopathy via electrodiagnostic study[ 13 , 14 ]. Chen et al [ 13 ] reported a case of segmental zoster paresis with electrodiagnostic findings of decreased amplitude in several nerves and ASA in clinically involved muscles[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies diagnosed segmental zoster radiculopathy via electrodiagnostic study[ 13 , 14 ]. Chen et al [ 13 ] reported a case of segmental zoster paresis with electrodiagnostic findings of decreased amplitude in several nerves and ASA in clinically involved muscles[ 13 ]. According to Liu et al [ 14 ], electrodiagnostic study of 8 segmental zoster paresis patients revealed low amplitude of CMAPs or sensory nerve action potentials with various ASA in all patients[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…HZ can lead to numerous complications, including postherpetic neuralgia, encephalitis, aseptic meningitis, and segmental zoster paresis (SZP). SZP is a rare complication of HZ that results in focal weakness of the extremity in the myotome that corresponds to dermatomal involvement [3][4][5]. SZP affects approximately 0.5% to 5% of patients with HZ [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…SZP is a rare complication of HZ that results in focal weakness of the extremity in the myotome that corresponds to dermatomal involvement [3][4][5]. SZP affects approximately 0.5% to 5% of patients with HZ [3,4].…”
Section: Introductionmentioning
confidence: 99%